Analysis of the Performance of Liquid Fertilization in Cucumber Cultivation - Gatot Pramuhadi; Ahmad Jaelani Sidik; Ahmad Musyafa Haljauhari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Liquid fertilization can be applied to cucumber plants, including using electric sprayers, electric sprayers and air blowers, and using the mist blower. The three sprayer units are capable of producing fine granules (droplets) that can enter the stomata of cucumbers. This study aims to compare the results of spraying performance using the three methods of liquid fertilization in cucumber cultivation. The research method used is indoor testing in the Sprayer Laboratory to determine the value of the performance parameters of each method of liquid fertilization and outdoor testing to apply liquid fertilizer droplets to cucumbers and determine their effect on the growth and production of cucumbers. The results showed that the first fastest appearance of the flower and the first fruit was in the treatment using electric sprayers and air blowers at 24.6 days after planting (DAP) and 31.5 DAP. This treatment also produces cucumbers with the largest diameter, length, and weight of the fruit of 2.97 cm, 26.10 cm, and 298.28 grams. The accuracy of the dose of liquid fertilization application using an electric sprayer and air blower is 63.41%, an electric sprayer of 59.56%, and the mist blower of 29.90%. Keywords: Air blower, Droplet, Electric sprayer, Mist blower, Sprayer